2019
DOI: 10.3389/fimmu.2019.02909
|View full text |Cite
|
Sign up to set email alerts
|

Underestimated Manipulative Roles of Mycobacterium tuberculosis Cell Envelope Glycolipids During Infection

Abstract: The Mycobacterium tuberculosis cell envelope has been evolving over time to make the bacterium transmissible and adaptable to the human host. In this context, the M. tuberculosis cell envelope contains a peripheral barrier full of lipids, some of them unique, which confer M. tuberculosis with a unique shield against the different host environments that the bacterium will encounter at the different stages of infection. This lipid barrier is mainly composed of glycolipids that can be characterized by three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 225 publications
(221 reference statements)
2
67
0
Order By: Relevance
“…Consistent with this hypothesis, we have shown that FasR is necessary for optimal intracellular multiplication of M. tuberculosis in macrophages, therefore confirming the role of cell wall components in the ability of the pathogen to survive and multiply intracellularly (Garcia-Vilanova et al, 2019). In addition, the lack of FasR impaired the normal in vitro replication of M. tuberculosis in minimal medium devoid of lipids.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with this hypothesis, we have shown that FasR is necessary for optimal intracellular multiplication of M. tuberculosis in macrophages, therefore confirming the role of cell wall components in the ability of the pathogen to survive and multiply intracellularly (Garcia-Vilanova et al, 2019). In addition, the lack of FasR impaired the normal in vitro replication of M. tuberculosis in minimal medium devoid of lipids.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with this hypothesis, we have shown that FasR is necessary for optimal intracellular multiplication of M. tuberculosis in macrophages, therefore confirming the role of cell wall components in the ability of the pathogen to survive and multiply intracellularly (Garcia-Vilanova et al, 2019). Persistence of the tubercle bacillus inside cells relies upon inhibition of phagosome maturation and acidification (Rohde et al, 2007).…”
Section: Discussionsupporting
confidence: 75%
“…The recruitment of the early endosome autoantigen (EEA1) protein to early phagosomes is an essential step in phagosome maturation that Mtb LAM is able to inhibit (Fratti et al, 2001). These excellent reviews provide a more in-depth overview on the activity of PIM/LM/LAM Mtb glycolipids (Vergne et al, 2014;Garcia-Vilanova et al, 2019).…”
Section: Pim Lm Lammentioning
confidence: 99%
“…This group of Mtb lipids is composed of the trehalose-containing lipids (Garcia-Vilanova et al, 2019). Probably the best known lipid within this group is the essential lipid trehalose dimycolate (TDM), also called "cord factor" because it is required for the cording phenotype of Mtb which was originally described by Robert Koch in 1882 (Glickman et al, 2000).…”
Section: Tdm Dat/pat Sl-1mentioning
confidence: 99%
See 1 more Smart Citation